Reduced graphene oxide-silicon interface involving direct Si-O bonding as a conductive and mechanical stable ohmic contact - Rahpeima, Soraya; Dief, Essam; Peiris, Chandramalika; Ferrie, Stuart; Duan, A.; Ciampi, Simone; Raston, C.L.; Darwish, Nadim (ROYAL SOC CHEMISTRY, 2020)
Metal-semiconductor junctions are essential contacts for semiconductor devices, but high contact junction resistance is a limiting operational factor. Here, we establish an ohmic contact of low resistance of <4 × 10−6Ω cm2between platinum and n-type Si (111)-H surfaces. This involved Si-O covalent bonding a monolayer of graphene oxide (GO) to the Si surface followed by electrochemical reduction to form reduced graphene oxide (rGO). Current-voltage plots demonstrate that the GO/rGO transformation is associated with a change from a rectifying to an ohmic contact. The process is a viable method for constructing semiconductor-rGO interfaces and demonstrates that GO/rGO monolayers can be used as active components in tuning the contact resistance of metal-semiconductor junctions.